Urban Farming Design Patterns in Landscape Architecture and the Influence of Marketing Innovation on Economic Sustainability in Malang City - Irawan Setyabudi; Eri Yusnita Arvianti; Retno Ayu Dewi Novita (Jurnal IPTEK, 2025)
This research analyzes the impact of marketing innovation on the economic sustainability of urban farming in Malang City. Urban farming has become an innovative solution in addressing issues of food security, the utilization of limited land, and the economic empowerment of urban communities. Using a quantitative approach, this research involved 86 urban farming practitioners selected through purposive sampling. The independent variables studied include product innovation, price innovation, and distribution innovation, while the dependent variable is the economic sustainability of urban farming. Data analysis using multiple linear regression shows that the three independent variables partially and simultaneously have a positive and significant effect on the economic sustainability of urban farming. Product innovation is the most dominant factor with a regression coefficient of 0.419 and a beta value of 0.517, followed by price innovation (coefficient 0.421, beta 0.307) and distribution innovation (coefficient 0.272, beta 0.211). The regression model has a coefficient of determination (R²) value of 0.713, indicating that 71.3% of the variation in the economic sustainability of urban farming is explained by these three independent variables. These findings indicate the importance of innovative approaches in marketing strategies to support the economic sustainability of urban farming in Malang City.